Self-schema and self-discrepancy mediate the influence of Instagram usage on body image satisfaction among youth. (March 2017) - Ahadzadeh, Ashraf Sadat; Pahlevan Sharif, Saeed; Ong, Fon Sim
Abstract: This study investigated the direct effect of Instagram usage on body satisfaction, whether this effect is mediated by appearance self-schema and self-discrepancy, and whether self-esteem moderates this effect. A total of 273 university students using Instagram were conveniently recruited to do the online survey on demographic characteristics, Instagram usage, self-schema, self-discrepancy, body satisfaction and self-esteem. Partial Least Squares Structural Equation Modeling was used to test the research hypotheses. As predicted, the results revealed that appearance self-schema and self-discrepancy mediated the effect of Instagram usage on body satisfaction. Moreover, this mediation effect varied depending on the Instagram users' self-esteem level, such that the negative effect of Instagram usage on body satisfaction through self-schema and self-discrepancy became stronger for those with a lower level of self-esteem. Highlights: Instagram usage has a negative effect on body satisfaction. Appearance self-schema has a significant positive influence on self-discrepancy. Self-schema and self-discrepancy mediate the effect of Instagram usage on body satisfaction. The Instagram usage on self-schema is stronger for with a lower level of self-esteem. Self-esteem moderates the influence of Instagram usage on body satisfaction.